PKM-KONSELING IBU HAMIL DALAM MEMENUHI KEBUTUHAN DASAR IBU SELAMA KEHAMILAN DI KELURAHAN BAGAN PETE - Melda Amalia (Jurnal Abdimas Kesehatan (JAK), 2019)
Maternal and infant mortality is very influential on the integrity and resilience of family and society, the quality of human resources, which in turn will hinder efforts to achieve national development goals. The causal factors that cause indirect or direct causes are because most pregnant women do not understand the physiological changes that occur during pregnancy so that the mother cannot adapt to physiological changes during pregnancy. The physiology of pregnancy and childbirth in general is the same, but because certain things related to the process of forming a fetus in the womb until the birth of a baby varies, the physiology of the baby's birth becomes different from one another. One of them is circulation function in pregnancy. Blood circulation from the mother for fetus will increase according to gestational age and according to the increase in weight and size of the fetus. The aim of this community service program is that expectant mothers can understand the basic needs during pregnancy both for the needs of the mother and the fetus. One effort that can be done so that the mother can understand the basic needs during pregnancy, both the needs for the mother and the basic needs for the fetus, namely by giving counseling explanations about what needs are needed by the mother and fetus.